1996
DOI: 10.2224/sbp.1996.24.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Implications of Adaption-Innovation: Ii. Adaption-Innovation and Motivation for Uniqueness

Abstract: The heuristic similarity between innovativeness and uniqueness motivation was investigated. Fifty-eight male and 107 female first-year undergraduates completed the Need for Uniqueness Scale (NUS; Snyder and Fromkin, 1980) and Kirton Adaption-Innovation Inventory (KAI; Kirton, 1976). As predicted, Innovators obtained significantly higher scores on uniqueness motivation than did Adaptors (p < .001), and Need for Uniqueness correlated substantially with Innovation (r=0.55). These findings provide support for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Importantly, the TAC has been derived from soundly developed factors that can be easily measured (Bowles, 2006(Bowles, , 2010 compared with other theoretical descriptions of behaviour and change. The TAC is also an advance on the single dimensional model of the link between innovation and adaptation proposed by Kirton (1976Kirton ( , 2000Skinner, 1989Skinner, , 1996Martin et al, 2012;Smith et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the TAC has been derived from soundly developed factors that can be easily measured (Bowles, 2006(Bowles, , 2010 compared with other theoretical descriptions of behaviour and change. The TAC is also an advance on the single dimensional model of the link between innovation and adaptation proposed by Kirton (1976Kirton ( , 2000Skinner, 1989Skinner, , 1996Martin et al, 2012;Smith et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…A second description of change typologies is provided by Kirton (, ), who argued that the adaptation theory is founded on the assumption that all people have to solve problems and that they differ in relation to how ordered and creative they are in doing so (Kirton, ). There are two typologies of change according to Kirton, with adaptive individuals at one end of the continuum and innovative individuals at the other (Kirton, , , ; Skinner, , ; Skinner & Drake, ; Smith, Hill, & Barber, ). The adaptors are individuals who use familiar techniques and use previously articulated strategies to guide the process to a solution.…”
mentioning
confidence: 99%
“…Given its grounding in concepts like autonomy and nonconformity, it is surprising that so little research has been done to link this concept with creativity. One study related the need for uniqueness to the concept of innovation (Skinner, 1996) and one Japanese study linked it to divergent thinking tasks (Okamoto & Takaki, 1992). Almost by definition, creators place great value on what is highly original and different from what has gone before.…”
mentioning
confidence: 99%
“…Previous research has shown t hat stable patterns of behavi or consistently distinguish adaptors from innovators (e.g., Carne & Kirton, 1982;Goldsmith, 1984;Keller & Ho lland, 1978;Kirton, 2000;Skinner, 1989Skinner, , 1996. Adaptors solve problems using familiar and clearly articulated techniques or st rategies; innovators are im patient with traditional procedures o r rules, preferring novel and r elatively unstructured methods for the solution of problems.…”
mentioning
confidence: 99%